Numerical investigation of long-term operation of ground-source heat pumps at neighborhood level: Focus on thermal interactions and electricity consumption. (November 2021) - Jaafar, Mohamad Ali; Maragna, Charles
Highlights: Long-operation of shallow geothermal energy is studied using non-linear programming. Interactions between borehole heat exchangers are studied with line source models. Ground-sourced heat pumps performance is computed dynamically. Fields interactions could be synergies depending upon climate and building use. A simplified and more efficient moving finite line source model is developed. Abstract: A comprehensive numerical investigation of long-term operation of Ground-Sourced Heat Pumps through Borehole Heat Exchangers is presented. Thermal fluxes between systems are analyzed through a semi-analytical method based on line source models. Operation points of geothermal and backup systems are determined by an hourly-based non-linear constrained optimization. Simulations of a 12-buildings neighborhood demonstrated that middle-buildings experience higher electrical consumptions than corner-buildings. Thermal interactions could be interferences or synergies decreasing or increasing GSHP performances, respectively, depending mainly on heating/cooling balance. Parametrical study showed that low Darcy velocities, insulated ground surface, shorter heat-exchangers, and denser and compact neighborhoods enhance thermal interactions impacts.